Different and rapid responses of four cyanobacterial psbA transcripts to changes in light intensity. - Bustos, S A (1990)
The genome of the cyanobacterium Synechococcus sp. strain PCC 7942 contains three psbA genes which encode two forms of the D1 protein of photosystem II. Experiments using psbA-lacZ translational fusions and Western blot (immunoblot) analysis have shown that the psbA genes respond differently to changes in light intensity, altering the ratio of the two forms of D1 in the thylakoid membrane. Each gene produces a 1.2-kilobase (kb) mRNA. A probe specific for psbAII transcripts also identified a 1.6-kb mRNA which starts 419 base pairs upstream of the 5' end of the 1.2-kb species and overlaps the entire 1.2-kb transcript. This 419-base-pair region includes an open reading frame (ORF1) of 114 amino acids. We investigated the effects of changes in light intensity on psbAII transcript levels in a series of light shift experiments in the wild-type Synechococcus sp. and in AMC084, a mutant which does not produce the 1.6-kb transcript. After exposure to high light intensities for 15 min, the level of the 1.2-kb psbAII transcript increased in both strains. This transcript was not detected in either strain after transfer to low light intensity. The psbAIII transcript showed the same pattern of response as the 1.2-kb psbAII transcript, whereas the 1.6-kb psbAII transcript was unaffected by different light intensities. The psbAI transcript levels responded oppositely to those of psbAII and psbAIII. These data, considered along with previous results obtained by using lacZ translational gene fusions, indicate that the response of psbA genes to changes in light intensity is controlled primarily at the transcriptional level.